A tiered area‐of‐review framework for geologic carbon sequestration. Issue 1 (27th December 2013) - Birkholzer, Jens; Cihan, Abdullah; Bandilla, Karl
Abstract This paper discusses the current guidance given by the United States Environmental Protection Agency (EPA) on delineating the so‐called Area of Review (AoR) for the permitting of geologic carbon sequestration (GCS) projects. According to the EPA's regulatory framework for GCS, the AoR refers to the region surrounding the CO2 injection well(s) wherein leakage of CO2 and/or the migration of formation fluids could possibly endanger overlying groundwater resources. Our evaluation of the current framework for delineating the size of this area finds unnecessary conservatism in the definition of the critical pressure, which could lead to a heavy burden on permit applicants that seek to get regulatory compliance, in particular for very large GCS projects. We propose a risk‐based re‐interpretation of this framework, separating the total Area of Review into different sub‐areas with different regulatory requirements depending on whether the concern is about free‐phase CO2 or pressure‐driven brine migration. This leads to a tiered AoR definition in which the projected region of CO2 plume extent would have the highest regulatory standards regarding site characterization, monitoring, and corrective action. The requirements in the AoR outside this central region would be less burdensome because of a narrower focus on major pathways for brine leakage such as unplugged wellbores and large faults. We expect that this revised framework would allow for a reduction in the cost of regulatory compliance for projects with very large injection volumes, while ensuring that the objective of protecting valuable groundwater resources is preserved.